2020
DOI: 10.1039/c9cc09630b
|View full text |Cite
|
Sign up to set email alerts
|

Spin transition in a ferrous chloride complex supported by a pentapyridine ligand

Abstract: Apparent high-spin complex with FeN5Cl coordination sphere exhibits a complete transition to the low-spin state on cooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…4. This value was 2.2 kcal mol −1 higher than what can be expected from the determined spin-transition temperature of the powder sample at 80 K. 15 As the solvated chloride-coordinated sample had remaining HS species down to 20 K, the B3LYP* calculations with 15% HF exchange should thus represent the complex in solution with relatively high accuracy. Calculations of the other complexes showed that they all favour high-spin states, even more so than iron, see Fig.…”
Section: Structures Of Divalent Metal Complexesmentioning
confidence: 77%
See 4 more Smart Citations
“…4. This value was 2.2 kcal mol −1 higher than what can be expected from the determined spin-transition temperature of the powder sample at 80 K. 15 As the solvated chloride-coordinated sample had remaining HS species down to 20 K, the B3LYP* calculations with 15% HF exchange should thus represent the complex in solution with relatively high accuracy. Calculations of the other complexes showed that they all favour high-spin states, even more so than iron, see Fig.…”
Section: Structures Of Divalent Metal Complexesmentioning
confidence: 77%
“…As we reported recently, this is due to a spin-state change (spin-crossover, SCO) from quintet 5 [Fe II -Cl] to singlet 1 [Fe II -Cl] that occurs at a temperature below 80 K in the microcrystalline powder sample. 15 To get closer to the conditions of the CV experiments, the XAS parameters were also obtained after dissolving the four samples in acetonitrile with electrolyte. The XAS spectra of the [Mn II -Cl], [Co II -Cl] and [Ni II -Cl] complexes remained unchanged as compared to the spectra recorded for the powder samples (see Fig.…”
Section: Structures Of Divalent Metal Complexesmentioning
confidence: 99%
See 3 more Smart Citations